Use of RUSH protocol to diagnose the type of shock in children - K. Yu. Ermolenko; K. V. Pshenisnov; Yu. S. Aleksandrovich; A. I. Konev; T. M. Kalinichenko; D. D. Lopareva; D. R. Rybakova; I. E. Gorbunov; L. O. Kiseleva (Вестник анестезиологии и реаниматологии, 2025)
Introduction. RUSH protocol (Rapid ultrasound in shock and hypotension) is a unique ultrasound examination algorithm that allows to establish the cause of systemic hypoperfusion and arterial hypotension in a critically ill patient in a minimum time, simultaneously with therapeutic interventions.The objective was to evaluate the effectiveness and clinical significance of the RUSH protocol in the practical activities of pediatric anesthesiology and intensive care units with an infectious profile for the purpose of early diagnosis of the shock type.Materials and methods. Twenty-five children who needed treatment in the intensive care unit were examined, the median age was 6.1 (1 month – 17 years) years. All were diagnosed with shock of various etiologies upon admission, 10 (40%) children required infusion of sympathomimetics. The average duration of mechanical ventilation was 7.45 (0–32 days) days, the duration of treatment in the intensive care unit was 11.5 (0–32 days) days. Death occurred in 9 (36%) children. All patients underwent ultrasound examinations using the RUSH protocol. Comparison of diagnoses was carried out between the initial physical examination data, the RUSH protocol results and the final diagnosis. Comparability in determining the type of shock by one observer was assessed using the kappa coefficient. Results. Excellent sensitivity, good specificity and maximum comparability with the final diagnoses were in hypovolemic shock (100% sensitivity and specificity). Good sensitivity and specificity were characteristic of cardiogenic shock. A sufficient level of compliance, excellent specificity, but low sensitivity were noted in distributive shock. In three patients, the RUSH protocol diagnosed a combined type of shock (sensitivity 100%), while the physical examination did not establish a diagnosis of shock depending on the leading link of pathogenesis.Conclusion. The RUSH protocol is an indispensable tool for screening ultrasound examination for diagnosing the type of shock in children with acute infectious diseases in critical condition.